Consumerism and Its Awareness In India: an Evaluative Study: Examining the State of Consumer Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In this paper an attempt is being taken toevaluate the present position of consumer rights in the field of business. Indoing so, the entire paper is divided in to three parts. ‘Evaluative Study onConsumer Rights in the Context of Business ’ provides a comprehensive study ofconsumer rights such as Various dimensions of consumer rights, Needs ofconsumer rights and Measures of protection. The Consumer Protection plays avital role to safeguard the interest of the consumers. In order to utilize thisAct to the maximum extent possible thorough awareness about various aspects ofthe act is essential. In this regard Government, Associations and Consumersshould come forward and try to improve the concept of consumerism. A consumeris a person who buys any goods or hires any service for valuable consideration.The term does not include a person who obtains goods or services for resale orfor any commercial purpose. However, persons who avail goods or servicesexclusively for the purpose of earning their livelihood by means ofself-employment are considered as ‘consumers’. Consumer must be aware of hisrights, raise voice against exploitation and seek redressal of his grievances.Consumers' consciousness determines the effectiveness of consumerism. In this paper an attempt is being taken toevaluate the present position of consumer rights in the field of business. Indoing so, the entire paper is divided in to three parts. ‘Evaluative Study onConsumer Rights in the Context of Business ’ provides a comprehensive study ofconsumer rights such as Various dimensions of consumer rights, Needs ofconsumer rights and Measures of protection. The Consumer Protection plays avital role to safeguard the interest of the consumers. In order to utilize thisAct to the maximum extent possible thorough awareness about various aspects ofthe act is essential. In this regard Government, Associations and Consumersshould come forward and try to improve the concept of consumerism. A consumeris a person who buys any goods or hires any service for valuable consideration.The term does not include a person who obtains goods or services for resale orfor any commercial purpose. However, persons who avail goods or servicesexclusively for the purpose of earning their livelihood by means ofself-employment are considered as ‘consumers’. Consumer must be aware of hisrights, raise voice against exploitation and seek redressal of his grievances.Consumers' consciousness determines the effectiveness of consumerism.